(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
This study aimed to investigate the impact of varying fibre compositions and fabric constructions on the elastic behaviour of compression fabrics. Knitted fabrics used as compression garments are subjected to deformation due to various loads used to extend the fabrics during wear. The loads to extend the fabrics are influenced by fabric constructions, strain levels and fabric directions. In this study, the strain of fabrics was measured using a commercial tensile testing machine (LR30K Lloyd) according to ASTM D496. Each sample was cycled five times between zero and the specified strain to replicate the repeated use of compression garments. In addition, the fabric was also heat-set and laundered to evaluate the impact of these treatments on the elastic behaviour of the fabric. The results indicated that different fabric constructions exhibited different elastic properties (P